Adoption of green credit policies by financial institutions. Critical analysis through data mining. - Bonilla Bonilla, Jhonny Fernando (2023)
The objective was to critically analyze the adoption of Green Credit policies by financial institutions. Through a bibliographic review of 19 selected scientific articles. Through data analysis, patterns and trends related to the policies studied were identified. The results showed that there is a growing interest in the adoption of these credits, especially in relation to government regulations and incentives and the criteria and standards for their implementation. The importance of Green Credits for sustainable development and the transition to a low-carbon economy was highlighted.